Youth breakdancers: profiling morphology and physical fitness characteristics - Zhao, Y.; Wei, X.; Zhao, K. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: This study aims (i) to profile the body composition, morphology and physical fitness characteristics of adolescent breakdancers aged 12 to 17 from a national training camp and (ii) to analyze whether these factors affected by the state of maturity (determined by years from peak height velocity) and (iii) to examine the validity of test battery for youth elite breakdancers. METHODS: Morphological attributes and selected physical fitness performance were measured on twenty-three male breaking athletes (14.47±1.95yrs). Biological maturational parameters (maturity offset) were calculated by linear equation based on peak height velocity and APHV were recorded. Information such as the athletes chronological age and training background is collected before the test. ANOVA was employed to examine the differences between different maturation groups, and Spearman Correlation Analysis was conducted to investigate intragroup correlation. RESULTS: Anthropometric variables, including height (F=23.957, p*0.01, *²=0.706), sitting height (F=25.279, p*0.01, *²=0.717), leg length (F=14.414, p < 0.01, *²=0.590) and body mass (F=14.429, p*0.01, *²=0.591) were significantly differentiated by APHV, and these measurements were correlated with jump (r=0.702, p*0.01 for height; r=0. 619, p=0.002 for sitting height; r=0.535, p=0.08 for body mass), 30m sprint (r=-0.670, p=0.004 for height; r=-0.636, p=0.008 for sitting height; r=-0.636, p=0.008 for body mass), 40m sprint (r=-0.540, p=0.031 for heigh), 50m sprint (r=-0.736, p=0.001 for height; r=-0.686, p=0.003 for sitting height; r=-0.707, p=0.002 for body mass), 30s push-up (r=0.495, p=0.019 for height; r=0.426, p=0.048 for sitting height; r=0.463, p=0.030 for body mass), 400m run (r=-0.638, p=0.001 for height; r=-0.584, p=0.003 for sitting height; r=-0.594, p=0.003 for body mass), and 1500m run (r=-0.423, p=0.044 for body mass; r=-0.647, p*0.01 for fat mass percentage). CONCLUSION: The height, weight and body fat percentage of adolescent breakdancers are relatively low which could be the result of specific choices. These morphological characteristics can prompt talent orientation. Furthermore, maturity levels can still forecast the different performance of athletes by the test battery in this study. Early-maturing athletes tend to excel in jumping, speed, and the 400m run. Coaches can use this to understand the adolescent development status of athletes. It is recommended that professionals continue researching more suitable field test components.